2021
DOI: 10.15420/cfr.2020.20
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of De Novo Heart Failure and Acute Decompensated Chronic Heart Failure: Are They Distinctive Phenotypes That Contribute to Different Outcomes?

Abstract: Heart failure is currently one of the leading causes of morbidity and mortality. Patients with heart failure often present with acute symptoms and may have a poor prognosis. Recent evidence shows differences in clinical characteristics and outcomes between de novo heart failure (DNHF) and acute decompensated chronic heart failure (ADCHF). Based on a better understanding of the distinct pathophysiology of these two conditions, new strategies may be considered to treat heart failure patients and improve outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 80 publications
0
11
3
Order By: Relevance
“…In our study, age and dyspnea were equable between both groups, as were the parameters of hemoglobin, white blood cell and platelet counts. Interestingly, a previous meta-analysis has indicated that a lower age of de novo AHF patients is likely; however, we did not observe such an association [23]. The inflammatory biomarkers, like C-reactive protein, IL-6 and IL-22, were also comparable between both groups, alongside several remodeling markers.…”
Section: Discussioncontrasting
confidence: 60%
“…In our study, age and dyspnea were equable between both groups, as were the parameters of hemoglobin, white blood cell and platelet counts. Interestingly, a previous meta-analysis has indicated that a lower age of de novo AHF patients is likely; however, we did not observe such an association [23]. The inflammatory biomarkers, like C-reactive protein, IL-6 and IL-22, were also comparable between both groups, alongside several remodeling markers.…”
Section: Discussioncontrasting
confidence: 60%
“…19 New onset heart failure: acutely worsened heart function without known underlying heart disease. 20 CV deaths: deaths that result from an acute myocardial infarction, sudden cardiac death, death due to heart failure, death due to stroke, death due to CV procedures, death due to CV hemorrhage, and death due to other CV causes. 21 Outcome: the occurrence of any of the major adverse CV outcomes and change in echocardiographic parameters in patients was correlated with volume overload determined by the methods described above.…”
Section: Methodsmentioning
confidence: 99%
“…New onset heart failure: acutely worsened heart function without known underlying heart disease. 20 5. CV deaths: deaths that result from an acute myocardial infarction, sudden cardiac death, death due to heart failure, death due to stroke, death due to CV procedures, death due to CV hemorrhage, and death due to other CV causes.…”
Section: Follow-upmentioning
confidence: 99%
“…myocarditis) or toxins. 6 These patients, despite a similar natural course and symptoms, tend to have a better prognosis than acutely decompensated chronic HF. In these patients, the typical mechanism is an acute haemodynamic derangement caused by LV systolic dysfunction.…”
Section: Clinical Approach To Acute Heart Failure: One Size Does Not ...mentioning
confidence: 99%
“…ADHF patients commonly present with pulmonary and/or peripheral congestion, left (and eventually right) ventricular dysfunction, and maladaptive neurohormonal activation in the context of a chronic illness in which exacerbations gradually reduce functional reserve, and in which mortality and HF chronicity are strictly interweaved. 6 Right ventricular dysfunction or frequent HF hospitalizations generally appear in advanced stages of the disease and should be considered as ‘red flags’ for adverse clinical outcomes. For example, in advanced HF patients, INTERMACS profiles take into account risk modifiers as frequent HF hospitalizations that define particularly high-risk situations; furthermore, recurrence of ventricular arrhythmias may denote an advanced state of the disease and is likewise considered a risk modifier due to its potential clinical relevance for patient management.…”
Section: Clinical Approach To Acute Heart Failure: One Size Does Not ...mentioning
confidence: 99%